2008
DOI: 10.1634/stemcells.2007-0599
|View full text |Cite
|
Sign up to set email alerts
|

Cardioinductive Network Guiding Stem Cell Differentiation Revealed by Proteomic Cartography of Tumor Necrosis Factor α-Primed Endodermal Secretome

Abstract: In the developing embryo, instructive guidance from the ventral endoderm secures cardiac program induction within the anterolateral mesoderm. Endoderm-guided cardiogenesis, however, has yet to be resolved at the proteome level. Here, through cardiopoietic priming of the endoderm with the reprogramming cytokine tumor necrosis factor ␣ (TNF␣), candidate effectors of embryonic stem cell cardiac differentiation were delineated by comparative proteomics. Differential two-dimensional gel electrophoretic mapping reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 89 publications
0
104
0
Order By: Relevance
“…[131][132][133] Because endoderm-derived signals are of crucial importance in cardiac development in vivo and drive cardiogenesis of ESCs in vitro, other investigators studied the endodermal secretome to identify factors guiding cardiac differentiation. 134 Based on the findings that secreted factors derived from tumor necrosis factor-␣-primed endoderm enhance cardiac commitment, an ongoing clinical study is addressing whether adult MSCs cultured with endoderm-derived factors improve cardiac function in patients with heart failure (C-Cure Trial, www.clinicaltrials.gov, NCT00810238).…”
Section: Enhancing Cardiac Regenerationmentioning
confidence: 99%
“…[131][132][133] Because endoderm-derived signals are of crucial importance in cardiac development in vivo and drive cardiogenesis of ESCs in vitro, other investigators studied the endodermal secretome to identify factors guiding cardiac differentiation. 134 Based on the findings that secreted factors derived from tumor necrosis factor-␣-primed endoderm enhance cardiac commitment, an ongoing clinical study is addressing whether adult MSCs cultured with endoderm-derived factors improve cardiac function in patients with heart failure (C-Cure Trial, www.clinicaltrials.gov, NCT00810238).…”
Section: Enhancing Cardiac Regenerationmentioning
confidence: 99%
“…94 -96 These studies have suggested potential pathways that could be activated in adult stem cells in an attempt to have them take on a cardiac phenotype. 94,96,97 Perhaps the most studied strategy to date with adult stem cells is the effect of 5-azacytidine, a DNA demethylation reagent, on cardiac protein expression in mesenchymal stem cells. 98,99 Several studies have demonstrated an increase in cardiac protein expression after treatment of mesenchymal stem cells with 5-azacytidine, and some have observed spontaneously beating cells.…”
Section: Directed Stem Cell Differentiation To Cardiac Myocytesmentioning
confidence: 99%
“…This will necessitate a cyclic return from molecular specificity to systematic physiological function, possibly with iterative incorporation of additional proteomic and other high-throughput data. As demonstrated by other extracellular proteomic 17 and combined metabolomic/proteomic 18 analyses, high-throughput identification and characterization of relationships between components of the extracellular domain can be critical in defining functional transitions between cellular states and cell fate decisions. Systems biology approaches offer an integrative approach by which to achieve data inclusivity and to maximize biological comprehension for disease diagnosis, determination of disease predilection, and assessment of therapeutic modalities, 3,5,19,20 and thus are ideally suited to addressing the biological complexity associated with future investigations into MMP isoform-dependent human ECM remodeling.…”
Section: Degradome Proteomicsmentioning
confidence: 99%